Preliminary Study of Duku's Peel Drying by Exposing Under Infrared Radiation Emitter - Laila Rahmawati; Hari Hariadi; Daniel Saputra; Kaprawi Sahim; Gatot Priyanto (AGROINTEK, 2022)
Duku (Lansium domesticum) is of tropical fruit which has a short shelf life of around 3-5 days at room temperature. There were many methods that were used to prolong the shelf life of duku, the one method that is commonly found is Modified Atmosphere Packaging (MAP). In the last decade, infrared is one of methods that had been implemented in food processing to securing and ensuring the foodstuff quality. There was a limited study reported about using infrared to prolong the shelf life, securing, and ensuring the quality of duku. In this preliminary study, duku was exposed using infrared emitter radiation (1000 watts), 10 cm of infrared distance, 400°C of temperature, and 50 seconds of exposing time. The result has shown the treatment could create a shell likeness on duku’s peel and could extend the shelf life of duku up to 2 weeks.